2022
DOI: 10.1007/s00464-021-08915-y
|View full text |Cite
|
Sign up to set email alerts
|

Outcome of ERCP related to case-volume

Abstract: Background and aims In some studies, high endoscopic retrograde cholangiopancreatography (ERCP) case-volume has been shown to correlate to high success rate in terms of successful cannulation and fewer adverse events. The aim of this study was to analyze the association between ERCP success and complications, and endoscopist and centre case-volumes. Methods Data were obtained from the Swedish National Register for Gallstone Surgery and ERCP (GallRiks) on a… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
4
1

Citation Types

1
5
0

Year Published

2023
2023
2024
2024

Publication Types

Select...
9

Relationship

1
8

Authors

Journals

citations
Cited by 11 publications
(6 citation statements)
references
References 34 publications
1
5
0
Order By: Relevance
“…A large retrospective study found that a low case volume was a risk factor for post-ERCP pancreatitis in certain scenarios. Syrén et al 15 performed a retrospective analysis of 80,904 ERCPs in Sweden between 2009 and 2018. Endoscopists with higher case volumes were noted to have lower rates of PEP when ERCPs were performed for choledocholithiasis (OR, 1.028; 95% CI, 1.002–1.054) and malignancy (OR, 1.179; 95% CI, 1.045–1.330).…”
Section: Post-ercp Pancreatitismentioning
confidence: 99%
“…A large retrospective study found that a low case volume was a risk factor for post-ERCP pancreatitis in certain scenarios. Syrén et al 15 performed a retrospective analysis of 80,904 ERCPs in Sweden between 2009 and 2018. Endoscopists with higher case volumes were noted to have lower rates of PEP when ERCPs were performed for choledocholithiasis (OR, 1.028; 95% CI, 1.002–1.054) and malignancy (OR, 1.179; 95% CI, 1.045–1.330).…”
Section: Post-ercp Pancreatitismentioning
confidence: 99%
“…A CBD stent can prevent further problems from arising and relieve symptoms like jaundice. The stent is usually implanted via an operation known as endoscopic retrograde cholangiopancreatography (ERCP), in which the bile ducts are accessed by passing a flexible tube equipped with a camera through the mouth, down the oesophagus, and into the stomach and small intestine [4].…”
Section: Introductionmentioning
confidence: 99%
“…Usually a benign anatomical variation, it might occasionally provide difficulties during gallbladder surgery or be linked to certain diseases like cholecystitis or gallstones [2,3]. A cholecystectomy, or surgical removal of the gallbladder, may be advised if the Phrygian cap is producing recurrent symptoms, complications such as gallstones or cholecystitis, or if there is a chance of issues in the future [4,8]. This can often be performed laparoscopically, which is less intrusive and heals more quickly than open surgery [3].…”
Section: Introductionmentioning
confidence: 99%
“…Visceral perforation and bleeding are sometimes seen after ERCP, but the most feared complication is that of post-ERCP pancreatitis (PEP), with a rate of 3.5%–5% ( 1 ). It has been suggested that higher endoscopist case volumes are associated with safer ERCP and successful outcomes, and therefore, there is an urgent need to provide opportunities for hands-on training for all endoscopists and surgeons performing ERCP ( 2 , 3 ).…”
Section: Introductionmentioning
confidence: 99%